Gonadal transcriptome sequencing reveals sexual dimorphism in expression profiling of sex-related genes in Asian arowana (Scleropages formosus) - Zhao, Chenxi; Bian, Chao; Mu, Xidong; Zhang, Xinhui; Shi, Qiong (Frontiers in Genetics, 2024)
Asia arowana (Scleropages formosus) is an ornamental fish with high economic value, while its sex determination mechanism is still poorly understood. By far, no morphological evidence or molecular marker has been developed for effective distinguishment of genders, which poses a critical challenge to our captive breeding efforts. In this study, we sequenced gonadal transcriptomes of adult Asian arowanas and revealed differential expression profiling of sex-related genes. Based on the comparative transcriptomics analysis of testes (n=3) and ovaries (n=3), we identified a total of 8,872 differentially expressed genes (DEGs) and 18,490 differentially expressed transposable elements (TEs) between male and female individuals. Interestingly, the expression of TEs usually has been more significantly testis-biased than related coding genes. As expected, several genes related to females (such as foxl2 and cyp19a1a) are significantly transcribed in the ovary, and some genes related to male gonad development (such as dmrt1, gsdf and amh) are highly expressed in the testis. This sexual dimorphism is valuable for ascertaining the differential expression patterns of sexrelated genes and enriching the genetic resources of this economically important species. These valuable genetic materials thereby provide instructive references for gender identification and oneto-one breeding practices so as to expand fish numbers for a rapid elevation of economic value.